2020
DOI: 10.1021/acs.jproteome.0c00072
|View full text |Cite
|
Sign up to set email alerts
|

Metagenome-Guided Proteomic Quantification of Reductive Dehalogenases in the Dehalococcoides mccartyi-Containing Consortium SDC-9

Abstract: At groundwater sites contaminated with chlorinated ethenes, fermentable substrates are often added to promote reductive dehalogenation by indigenous or augmented microorganisms. Contemporary bioremediation performance monitoring relies on nucleic acid biomarkers of key organohalide-respiring bacteria, such as Dehalococcoides mccartyi (Dhc). Metagenome sequencing of the commercial, Dhccontaining consortium, SDC-9, identified 12 reductive dehalogenase (RDase) genes, including pceA (two copies), vcrA, and tceA, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
23
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(23 citation statements)
references
References 48 publications
(111 reference statements)
0
23
0
Order By: Relevance
“…have to scavenge adequate amounts of complete cobamides or precursor molecules to enable the maturation of RDases for energy conservation. For laboratory cultivation of Dehalococcoidia isolates, B 12 has been commonly supplied in the range of 25–50 μg L –1 . ,, During growth with TCE, targeted proteomic analysis quantified averages of 7.6 × 10 3 and 1.8 × 10 3 TceA proteins per Dhc cell in consortium KB-1 and consortium SDC-9, respectively. , Assuming each TceA protein contains one cobamide molecule (i.e., a 1:1 ratio), , the theoretical B 12 demand to reach the observed cell densities (Table ) would be 0.5–2.4 and 0.3–2.7 μg L –1 for Dhc strain FL2 and strain 195, respectively (eq ). …”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…have to scavenge adequate amounts of complete cobamides or precursor molecules to enable the maturation of RDases for energy conservation. For laboratory cultivation of Dehalococcoidia isolates, B 12 has been commonly supplied in the range of 25–50 μg L –1 . ,, During growth with TCE, targeted proteomic analysis quantified averages of 7.6 × 10 3 and 1.8 × 10 3 TceA proteins per Dhc cell in consortium KB-1 and consortium SDC-9, respectively. , Assuming each TceA protein contains one cobamide molecule (i.e., a 1:1 ratio), , the theoretical B 12 demand to reach the observed cell densities (Table ) would be 0.5–2.4 and 0.3–2.7 μg L –1 for Dhc strain FL2 and strain 195, respectively (eq ). …”
Section: Discussionmentioning
confidence: 99%
“…Although data for corrinoid types and concentrations in groundwater aquifers are not available, the indigenous corrinoid pool is unlikely to meet Dhc strains’ μg L –1 level B 12 demand to achieve maximum growth yields and dechlorination activity. Groundwater monitoring data indicated that meaningful in situ dechlorination activity and ethene formation can be achieved when Dhc cell titers exceed 10 6 L –1 . , Assuming 1.8 × 10 3 to 7.6 × 10 3 RDase (e.g., TceA) proteins per Dhc cell , and a cobamide-to-RDase molar ratio of 1:1, 8.1 to 34 pg L –1 of B 12 should theoretically meet the corrinoid demand of 10 6 Dhc cells L –1 and allow in situ bioremediation to take place. Therefore, it is conceivable that in situ aquifer conditions exist that sustain Dhc reductive dechlorination activity even at meager (i.e., ng L –1 ) corrinoid pool sizes.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…To this aim, metagenomics approaches provide reliable information about the key enzymes/genes involved in the degradation and detoxification of environmental pollutants to understand better the microbial community structure, functions, and interactions in contaminated matrices or engineered systems for the biological removal of pollutants, with implications for process optimization and bioremediation application at field scale ( Bharagava et al, 2019 ; Lapidus and Korobeynikov, 2021 ). Metagenomic studies have been previously conducted on stable dechlorinating consortia to shed light on the metabolic features of the microbial components and their role in the RD processes under different conditions ( Brisson et al, 2012 ; Maphosa et al, 2012 ; Dam et al, 2017 ; Wang et al, 2019 ; Kucharzyk et al, 2020 ). Similarly, some metagenomic studies have also been conducted on biological systems for Cr(VI) removal to explore the metabolic potential, including Cr(VI) remediation genes, primarily in wastewater treatment systems or microbial consortia ( Miao et al, 2015 ; Sun et al, 2019 ; Pei et al, 2020 ; Rahman and Thomas, 2021 ).…”
Section: Introductionmentioning
confidence: 99%
“…SDC-9 culture contains strains of D. mccartyi with pceA , tceA , and vcrA reductive dehalogenase genes. , …”
Section: Methodsmentioning
confidence: 99%